1981
DOI: 10.1007/bf00541155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between serum ferritin, anemia, and disease activity in acute and chronic rheumatoid arthritis

Abstract: The assessment of anemia in patients with rheumatoid arthritis may be difficult, especially when iron deficiency and the anemia of chronic disease coexist. The development of a radioimmunoassay for serum ferritin concentration has aided the detection of reduced body iron stores in uncomplicated iron deficiency, but its use is compromised in clinically active rheumatoid arthritis by the tendency of serum ferritin to behave as an acute phase reactant. In this latter role it correlated well with disease activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

1986
1986
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 7 publications
0
9
1
Order By: Relevance
“…Therefore values of hemoglobin were influenced by relatively short duration of minimal exercise causing plasma dilution. Furthermore, ferritin values could be higher than baseline after period of stress, because of ferritin being an acute phase reactant [28]. Yet, our results as well as the results of the studies performed in active athletes failed to show an increase in serum ferritin after period of short exercise [29].…”
Section: Discussioncontrasting
confidence: 69%
“…Therefore values of hemoglobin were influenced by relatively short duration of minimal exercise causing plasma dilution. Furthermore, ferritin values could be higher than baseline after period of stress, because of ferritin being an acute phase reactant [28]. Yet, our results as well as the results of the studies performed in active athletes failed to show an increase in serum ferritin after period of short exercise [29].…”
Section: Discussioncontrasting
confidence: 69%
“…For example, several studies show that serum ferritin levels in active RA did not dier from those in healthy people, but the mechanism for this was not clear [15]. Our study revealed that SLE patients exhibited higher serum ferritin levels than RA patients, whose levels were within the normal range but lower than those in the more active stage of SLE (SLEDAI 10, group C) but showed no signi®cant differences from less active stages (SLEDAI <10, groups A and B).…”
Section: Discussionmentioning
confidence: 93%
“…5,34,35 Ferritin released into the blood as an acute-phase reactant due to inflammation, anemia of chronic disease, or malignancy is typically apoferritin and has low iron content, 5,34,35 especially ferritin molecules released from cells or tissues that do not typically store iron. 9,11,15,16 Interleukin-1 and ethanol enhance the production and secretion of apoferritin. 12,13 Uncertainties of the present work include the possibility that some participants had undiagnosed diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Geometric mean SF levels among male or female participants with the C282Y/H63D, H63D/H63D, C282Y/ + , and H63D/ + genotypes were not significantly different than the levels among male or female participants, respectively, with the wild-type HFE genotype. 7 SF is also increased in association with inflammation (including common liver disorders) [9][10][11][12][13][14] and neoplasms. 15,16 The aim of this study was to determine the relationships of SF to insulin resistance (determined by homeostasis model assessment of insulin resistance, HOMA-IR) 17 and the metabolic syndrome 18 in a cohort enriched with persons who had hemochromatosis, iron overload, and hyperferritinemia.…”
Section: Introductionmentioning
confidence: 99%